Analisis Kemandirian Keuangan Daerah (Studi Kasus: Provinsi Banten Tahu 2011-2015) - Joko Tri Haryanto (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
Decentralization is aimed to cut off the bureaucratic chains of public services while at the same time seeking for an independency aspect. One of its policies through regional expansion includes Banten Province. Unfortunately, the expansion of regions is actually synonymous with negative things, especially related to regional financial performance. For this reason, this research is conducted to get an overview of financial performance of Banten Province 2011-2015. This research is important to associate with Banten Province position as a buffer of the state capital in megapolitan development concept, while limiting only from Local Budget performance analysis. Using the ratio of regional financial independence, the conclusion is Banten Province has regional financial independency as well as very high on the the degree of fiscal decentralization. Only in Lebak District, Pandeglang District and Serang Municipal are still at very low level of independency. For the effectiveness of local own resources as well as local taxes, effectiveness in all regions is above 100%. This means that the effectiveness is very high and become one of the best in national level. This condition should be the best opportunity for the Banten provincial government as a form of local wisdom as an alternative formation of social capital for regional development. This enormous social capital should be able to process and use as regional development capital in the future combined with an integrated development planning pattern. Keywords: regional financial performance, local own resources, regional independency, fiscal decentralization